Membrane vesicles from Red Complex bacteria: key players in oral pathogenesis, immune disruption, systemic diseases, and therapeutic insights - Mahendrarajan, Venkatramanan; Lazarus, Huldah Pearlin Sarah; Muthukaliannan, Gothandam Kodiveri; Varghese, Sheeja; Easwaran, Nalini (Frontiers in Oral Health, 2025)
The oral cavity serves as a habitat for a diverse array of microorganisms, each performing distinct functions, thereby constituting a vibrant and intricate ecological community. The most common pathogenic bacteria in the oral ecosystem are the Red Complex group, which includes Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia. These bacteria have several ways to inflict damage, such as creating biofilms and secreting nano-sized vesicles from their outer membrane, called Outer Membrane Vesicles (OMV). OMVs are nano structures that carry proteins, lipids, and toxins from the outer membrane of Gram-negative bacteria. The OMVs of Red Complex bacteria play a role in the onset and development of oral pathological conditions such as gingivitis and periodontitis. Additionally, a substantial body of evidence supports the notion that these OMVs may exert influence on systemic pathologies, including atherosclerosis, alzheimer's, rheumatoid arthritis, and diabetes mellitus. This review will discuss the formation and composition of Red Complex bacterial OMVs, their impacts on the oral environment, the immune response, and their correlations with various systemic diseases. The suggested treatment approach by probiotics and bioactives focuses on the genetic elements that induce the production of OMVs by the Red Complex bacteria, offering a potent means to hinder the advancement of diseases propagated through these OMVs.